Odin in Daukantas’s Pantheon - Bončkutė, Roma (Senoji Lietuvos literatūra, 2024)
The article discusses the idea, proposed by Simonas Daukantas (1793–1864), that Odin was the second moderniser of the Lithuanian/Baltic society of the second century BC. The article first examines Daukantas’s interest in Odin’s history and introduces Daukantas’s extracts from various sources. Daukantas outlined the information about archaeological findings near the Black Sea, which are evidence of previous contacts of local inhabitants, in particular from Crimea, with the peoples on the Baltic coast (amber jewellery), about stone records with the names of Hermes and Mercury, about Odin’s origin, migration, and religion. Daukantas’s notes from the books he had read show that he was familiar with the comparative studies on the Eastern and Germanic-Scandinavian mythologies published in Europe at the end of the eighteenth century and in the first decades of the nineteenth century. Daukantas was influenced by the interest of the German Romantics in Scandinavian mythology and its comparison with the Germanic tradition.The article discusses how Odin is depicted in BUDĄ Senowęs-Lëtuwiû Kalnienû ĩr Ƶámajtiû (The Character of the Early Lithuanians, Samogitians, and Highlanders;1845). He used Geschichte Preußens (The History of Prussia; 1827, vol. 1) by Johannes Voigt (1786–1863) to support the idea that Odin was a shared Scandinavian-Baltic hero. Resorting to the works of the Danish-Norwegian historian Peter Friedrich von Suhm (1728–1798), Voigt claimed that Odin founded Asgard near the Daugava River.The article for the first time compares the figure of Odin as envisioned by Daukantas with the source from the 1826 edition of the Le Catholique magazine. Based on the article ‘De l’ère primitive des législations sacerdotales’ about the pagan priests of primitive societies, published in the first issue of this magazine, Daukantas portrays Odin as the creator of new laws and religions in the Lithuanian/Baltic society, which worshiped one supreme god Tėvūnas (Father), also called Perūnas (Thunder). One of the most significant arguments is that there are still people living today in Lithuania and Samogitia who have the surname ‘Odinas’. Daukantas’s mother herself was Odinaitė. Having introduced Odin to the pantheon of Lithuanian cultural heroes, Daukantas linked his individual mythology to Odin, who was considered to have been not only a talented warlord, a creator of new societal laws, a reformer of the institution of pagan priests, but also an inventor of writing, a poet, and an excellent orator. The possible kinship Daukantas perceived to have had with Odin allowed him to create an individual mythology and, supposedly, consider himself a unique historian charged with the special task of rescuing Lithuanians from stagnation by recalling their glorious past.
Keywords: Simonas Daukantas; Odin; legendary history; sources; cultural hero; mythology